"Are We There Yet?" The challenge of Public Engagement with Australia's Indigenous Past and its Implications for Reconciliation. (24th September 2015) - Muller, Stephen
Abstract : The proposition "We are all archaeologists now", appears to equate public interest in the past with the practice, theory and method of archaeology. To argue that this is not the case is not to adopt an elitist position but rather to consider the complexities of such a statement. The importance of public involvement in archaeology is acknowledged as both supporting, broadening and democratising the profession and the discussion of past lives and cultures. However, the limitations of generalised archaeological presentations, particularly as often presented in the general media is highlighted, noting that the ethical dimensions of archaeological practice is often ignored in favour of a methodological focus and attached with western bias. The application of an Australian context questions both the applicability and indeed relevance of the proposition to Traditional Owners for whom archaeological approaches may be viewed through the prism of past western cultural treatment and exploitation. Consequently the use of 'we' as an inclusive term is debatable within this contested cultural dimension. The limits of a general Australian public engagement and interest in Indigenous archaeology further undermines the proposition, although the potential for archaeology to play a positive ongoing role in promoting and supporting a reconciliation of these issues of understanding in collaboration with Traditional Owners is advocated. We may not all be archaeologists then, but we all have a stake in and role to play for a greater mutual understanding of the past and its effects on the present, with a view to the preservation of our collective cultural heritage.